Comparison of leaf osmotic adjustment expression in wheat (Triticum aestivum L.) under water deficit between the whole plant and tissue levels - Nio, Song Ai; Ludong, Daniel Peter Mantilen; Wade, Len J. (Agriculture and Natural Resources, 2018)
This study compared osmotic adjustment (OA) expression and solutes involved in leaves of wheat with high OA capacity (cv. Hartog) under water deficit (WD) in the glasshouse (whole plant level) and laboratory (tissue level). WD was applied at the reproductive stage for the whole plant level and WD was induced at the tissue level using polyethylene glycol (PEG) 8000 as a non-permeating osmotic agent. In the whole plant Experiment, leaf OA was expressed at 16 days (0.26 MPa) and increased to 0.37 MPa at 37 days of treatment. In the tissue level experiment, exposure of leaf segments to PEG 8000 treatments of 0, -0.5, -1.0 and -1.5 MPa and sampling times of 0, 12, 24, 48 and 72 h showed that the maximum leaf OA (0.37 MPa) was expressed on PEG -0.5 MPa after 48 h of treatment. K+, glycinebetaine and proline accounted for 21, 19 and 21% of OA in the glasshouse experiment. K+ did not contribute to the OA, while Na+ and proline only accounted for 5 and 1% in the laboratory experiment. Although OA was expressed in leaf segments of wheat subjected to WD under PEG -0.5 MPa, the laboratory-based PEG method with leaf segments could not substitute for the glasshouse experiment for screening germplasm for OA capacity.